Constraints on the Lithospheric Kinematics in the Aegean and Western Anatolia Unveiled by SKS Splitting Observations. Issue 12 (10th December 2022) - Erman, C.; Yolsal‐Çevikbilen, S.; Eken, T.; Tilmann, F.; Keleş, D.; Taymaz, T.
Abstract: The present study investigates azimuthal anisotropy and its relation to the geodynamical processes beneath the back‐arc of the Hellenic subduction zone in the eastern Aegean and western Anatolia where surface tectonics is dominated by the right‐lateral strike‐slip North Anatolian Fault Zone (NAFZ) in the north and E‐W oriented normal fault systems. We obtained apparent SKS splitting parameters from 1, 660 good quality and 137 null measurements extracted from 542 events recorded at 40 permanent broadband seismic stations. Overall, the station‐averaged splitting parameters indicate NNE‐SSW oriented fast directions (∼N20°E) and splitting delays around ∼1.5 s. The large splitting delays, particularly observed beneath the northern Aegean can be explained by either an enlarged mantle wedge thickness or increased strength of upper mantle anisotropy. We constrain complex anisotropy structures within two layer models from notable backazimuthal variations in individual splitting measurements observed beneath a few stations at the north located in a close proximity to the NAFZ and central‐western Anatolia. At the western end of the NAFZ, our estimated upper layer anisotropy direction (at ∼120 km) is rather parallel to the NAFZ reflecting the imprint of a lithospheric petrofabric formed by recent deformation while in central‐western Anatolia they correlate well with maximum shear directions and small splitting delays (∼0.6 s) appear to further support relatively thin lithosphere (∼90 km). An overall pattern of extension‐parallel fast directions (N10°E) within lower layer can be attributed to the slab rollback‐induced mantle flow that is highly oblique with respect to the WSW‐ward motion of the Anatolian lithosphere. Plain Language Summary: Seismological constrains on uppermost mantle structures provide essential information for better understanding of the geodynamic processes that have shaped the current deformation in complex tectonic regions. To investigate the seismic anisotropy, which is the directional dependence of seismic wave velocities, and its relation to the geodynamical processes in the upper mantle of eastern Aegean and western Anatolia, we performed splitting measurements on core‐mantle refracted shear waves recorded by 40 permanent broadband seismic stations. We overall estimate NE‐SW oriented fast polarization directions, and delay times between 0.65 and 2.2 s. The results imply that the origin of observed seismic anisotropy can be mostly explained by a combined effect of an internal deformation of the mantle lithosphere and asthenosphere. Our findings reveal the presence of two‐layer anisotropy outlining complicated structures, primarily in the upper mantle of NW Anatolia associated with the western end of North Anatolian Fault Zone. Future numerical modeling and anisotropy studies should be considered to test these results for further interpretation. Key Points: Observed seismic anisotropy can be explained by a combined effect of internal deformation of the mantle lithosphere and asthenosphere The presence of two‐layer anisotropy is obtained beneath the upper mantle of NW Anatolia A distinct counter‐clockwise rotation of average fast polarization directions from north to south of the Aegean region is estimated